2006
DOI: 10.1002/jor.20243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diurnal hyperosmotic loading on the metabolism and matrix gene expression of a whole‐organ intervertebral disc model

Abstract: It is generally agreed that the mechanical environment of intervertebral disc cells plays an important role in maintaining a balanced matrix metabolism. The precise mechanism by which the signals are transduced into the cells is poorly understood. Osmotic changes in the extracellular matrix (ECM) are thought to be involved. Current in-vitro studies on this topic are mostly short-term and show conflicting data on the reaction of disc cells subjected to osmotic changes which is partially due to the heterogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 53 publications
(57 reference statements)
7
47
2
Order By: Relevance
“…In agreement with our findings (data not illustrated), Ishihara and colleagues observed an increase of sulphated GAG synthesis in bovine NP cells with increase in osmolarity. 6 In an organ culture system, Haschtmann and colleagues found that an increase in osmolarity induced a (tendential) upregulation of aggrecan and downregulation of collagen I expression, 16 similar to our findings. Studies on articular chondrocytes showed that extracellular osmolarity influenced matrix synthesis and regulated aggrecan promoter activity as well as aggrecan expression and sulphated GAG synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our findings (data not illustrated), Ishihara and colleagues observed an increase of sulphated GAG synthesis in bovine NP cells with increase in osmolarity. 6 In an organ culture system, Haschtmann and colleagues found that an increase in osmolarity induced a (tendential) upregulation of aggrecan and downregulation of collagen I expression, 16 similar to our findings. Studies on articular chondrocytes showed that extracellular osmolarity influenced matrix synthesis and regulated aggrecan promoter activity as well as aggrecan expression and sulphated GAG synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…Cell volume changes could affect various membrane ion transporters and alter cell metabolism, resulting in a different biosynthetic activity of the cell [35,116]. Furthermore, studies have shown that osmolality and pH directly affect IVD cell metabolism [12,18,27,37,115,129].…”
Section: Indirect Stimulusmentioning
confidence: 99%
“…Due to the lack of appropriate animal models for endplate trauma, we used an in vitro organ culture approach, which is based on our recent work. There we established a whole-organ rabbit disc/endplate in vitro culture system with the possibility to keep the disc specimens in culture for more then 7 weeks without a significant loss of cell viability and proteoglycans from the extracellular matrix [19,20]. For the current study, we constructed a dropped-weight device for the sterile induction of endplate burst fractures and an accompanying injury of the adjacent intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…The disc/endplate specimens were dissected as described before [19,20]. After harvest the specimens (n = 10 per animal) were washed with agitation overnight in DMEM/F12 media (Labforce, Nunningen, Switzerland) with 50 lg/ml gentamicin (Labforce) and 10% FCS and 20 mmol sodium citrate.…”
Section: Induction Of Endplate Fracture and Disc Traumamentioning
confidence: 99%
See 1 more Smart Citation